Representasi Kesedihan dalam Video Klip "Lagu Duka" Karya Payung Teduh (Analisis Semiotika Roland Barthes) - Ronfiansyah, Dimas Dany Malik (Journal of Management, Education and Communication, 2024)
This research aims to analyze the representation of sadness in the video clip “Lagu Duka” by Payung Teduh. The research method uses media text analysis of Roland Barthes' semiotic analysis model, focusing on Barthes' three stages of analysis, namely denotation, connotation, and myth as a form of cultural meaning contained in the sign. This research approach uses critical analysis. The results show that sadness is represented through visual symbols such as dark colors, gloomy facial expressions, slow motion, and the use of objects that imply loss and emptiness. So that it feels the grief that is being experienced, the guilt that is being felt, the hopes that are not realized and the deep sense of disappointment. At the mythical level, sadness in this video is not only interpreted as a personal emotion, but as a reflection of collective grief and the bitterness of life.